Plants as Modifiers of Cadmium Bioavailability - Hale, B.; Berkelaar, E.; Chan, D.; Black, W.; Johnson, D. (Geoscience Canada, 2001)
Summary Estimating maximum metal concentrations for soils that protect both plant and human health is difficult, because plants can influence the amount of metal that is absorbed from soils or foods. Plant root accumulation of Cd, as well as translocation to shoots, is determined by internal physiological processes, and is not dependent on the free ion concentration of Cd in the growing medium. Absorption of Cd from edible plants by the kidney orliver is proportional to the dose, and is only slightly dependent on the form of Cd in the diet. Plants dominate the biomass (and thus the diets) in many ecosystems; their physiological processes must be considered in efforts to understand the transfer of metals among compartments of the environment.